Water Dynamics in Nanoporous Silica: Ultrafast Vibrational Spectroscopy and Molecular Dynamics Simulations - Yamada, Steven A; Shin, Jae Yoon; Thompson, Ward H; Fayer, Michael D (Journal of physical chemistry. C, 2019)
Nanoporous silica materials are important in catalysis, energy, and materials applications in which water is an essential component. System performance is intimately connected to the water dynamics occurring in the confined environment. However, the dynamics and associated structures of water in nanoporous silica have proven challenging to measure and predict. Here, confined water dynamics are examined via the ultrafast infrared spectroscopy of selenocyanate (SeCN–) dissolved in the hydrated ∼2.4 nm silica mesopores of MCM41. Polarization selective pump–probe and two-dimensional infrared measurements on the CN stretching mode of SeCN– are used to probe the effect of confinement on orientational relaxation and spectral diffusion dynamics. The dynamics of SeCN– provide information on the surrounding water hydrogen bond dynamics. The long CN stretch lifetime (∼36 ps), relative to the water hydroxyl stretch (<2 ps), significantly extends the time scales that can be accessed. Complete orientational relaxation (C 2(t), orientational correlation function) and spectral diffusion (C ω(t), frequency–frequency correlation function) dynamics are presented and compared to the simulated time correlation functions in a model silica pore of the same size. A slow decay component not present in the bulk liquid is observed in both experiments, indicating that the hydrogen bond dynamics are significantly altered by confinement. The simulations reveal a qualitative difference in the functional dependence of C 2(t;d) and C ω(t;d) on d, the distance from the interface. The former becomes exponentially faster with distance while the latter makes an abrupt transition from slower to faster dynamics midway between the surface and pore center, d ≅ 6 Å.